Workforce or workfare? - Craig Brett; Laurence Jacquet (Center for Economic Studies and ifo Institute (CESifo), 2011)
This article explores the use of workfare as part of an optimal tax mix when labor supply responses are along the extensive margin. Particular attention is paid to the interaction between workfare and an earned income tax credit, two policies that are designed to provide additional incentives for individuals to enter the labor force. This article shows that, despite their common goal, these policies are often at odds with each other.
Keywords: H21; 330; extensive margin; optimal income taxation; workfare; Optimale Besteuerung; Einkommensteuer; Aktivierende Sozialhilfe; Negative Einkommensteuer; Theorie